Knee pad and knee joint protection method

By designing a knee pad device that includes temperature control components and fit components, the existing knee pads are solved, and the unreasonable temperature distribution and unreasonable pressure distribution are achieved in cold or hot compresses, and the uniform adjustment of the knee surface temperature and optimization of pressure distribution are achieved, which significantly improves the efficacy and comfort of knee pads.

CN119868043APending Publication Date: 2025-04-25宗小锐
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202510032905.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-09
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The existing knee pads have great limitations in the functions of cold or hot compress, and cannot achieve uniform distribution of the surface temperature of the knee joint. Local overheating or supercooling often occurs, which affects the efficacy and may lead to tissue damage.

Method used

A knee brace device including a temperature control assembly and a fitting assembly is designed. The temperature control assembly consists of a heating plate, a refrigeration plate, a controller, a pressure sensor, a thermal imager and a display screen. Through the coordinated work of these components, uniform temperature adjustment and pressure distribution optimization within the knee brace are achieved.

Benefits of technology

The uniform distribution of the surface temperature of the knee joint is achieved, local overheating or overcooling is avoided, the efficacy of cold/heat compresses and the comfort of use are significantly improved, and the protection effect of the knee joint is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119868043A_ABST
    Figure CN119868043A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of kneecaps, and discloses a kneecap and a knee joint protection method.The kneecap comprises a kneecap body, a connecting belt is fixed to the outer wall of the kneecap body, a male buckle is fixed to the end of the connecting belt, a female buckle is fixed to the outer wall of the kneecap body, and a protection plate is fixed to the outer wall of the kneecap body; the temperature control assembly is arranged in the kneecap body and used for controlling the temperature in the kneecap; the temperature control assembly is arranged on one side of the interior of the kneecap body and used for controlling the temperature of the kneecap body, the attaching assembly is arranged on the other side of the interior of the kneecap body and used for improving the attaching effect of the kneecap body, the temperature control assembly comprises a plurality of heating plates and a plurality of refrigeration pieces, and the heating plates and the refrigeration pieces are fixed into the kneecap body. Through the cooperation between the temperature control assembly and the internal structure of the attaching assembly, the effect of heating or cooling the interior of the kneecap is achieved, some treatment effects are provided, meanwhile, the overall experience of a user is improved through the design of the honeycomb filling layer, and the problem that temperature conduction is not uniform in the cold / hot compress process of an existing kneecap is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of knee pads, in particular to a knee pad and a knee joint protection method. Background Art

[0002] In order to prevent injuries such as sprains of the hand joints, foot joints or knee joints, emergency treatment of these injuries, assisting in rehabilitation from injury to full recovery, or preventing recurrence of injuries, etc., a bandage (a stretchable or non-stretchable adhesive tape that fits the body) or bandage, a roughly cylindrical protective gear woven by circular knitting is used. Common knee pads are mainly made of a single material, mostly elastic fabrics or sponge fillings, and have a certain degree of support and comfort.

[0003] There are great limitations in the cold compress or hot compress functions. This type of knee brace cannot achieve uniform distribution of temperature on the surface of the knee joint, and usually causes local overheating or overcooling, which not only affects the therapeutic effect, but may also cause discomfort to the patient or even tissue damage.

[0004] Existing knee braces generally lack precise adaptation to the anatomical structure of the knee joint in design. Traditional flat or curved surface designs cannot dynamically match the complex curves of the knee joint, and are prone to local pressure concentration or knee brace slippage, especially during exercise. This problem directly affects the fit and support effect of the knee brace, and the user experience is poor, especially for users who are recovering from surgery or wearing it for a long time. Summary of the invention

[0005] In view of the deficiencies in the prior art, the present invention provides a knee pad and a knee joint protection method, which solves the significant limitations of the knee pad in terms of cold compress or hot compress functions. This type of knee pad cannot achieve uniform distribution of surface temperature of the knee joint, and usually causes local overheating or overcooling.

[0006] To achieve the above objectives, the present invention is implemented through the following technical solutions: a knee pad device, comprising: A kneepad body, the outer wall of which is fixed with a connecting belt, the end of which is fixed with a male buckle, the outer wall of the kneepad body is fixed with a female buckle, and the outer wall of the kneepad body is fixed with a protective plate; A temperature control component is arranged inside the kneepad body and is used to control the temperature inside the kneepad; A fitting component, which is arranged on the other side of the inner part of the kneepad body and is used to improve the fitting effect of the kneepad; The temperature control component includes multiple heating plates and multiple cooling plates, which are fixed inside the knee pad body. A controller is fixed inside the knee pad body. A pressure sensor is fixed inside the knee pad body. The pressure sensor and the controller are electrically connected. A thermal imager is fixed inside the knee pad body. A display screen is fixed on the outer wall of the knee pad body. The display screen and the thermal imager are electrically connected.

[0007] Furthermore, the kneepad body is fixed by connecting straps, male buckles and female buckles, while the external protective plate provides additional mechanical protection for the knee joint. The heating plate and cooling plate of the temperature control component are switched and adjusted by the controller, which can accurately achieve heating or cooling inside the kneepad. The pressure sensor monitors the pressure distribution of the knee joint in real time and transmits the data to the controller. The thermal imager collects the temperature distribution of the knee joint in real time, and the display provides intuitive feedback to the user. The overall device solves the problems of uneven temperature and unreasonable pressure distribution during the cold / hot compress process of the kneepad through the collaborative work of multiple components, while improving the wearing comfort.

[0008] Preferably, the fitting component includes a protective pad 1, the outer wall of the protective pad 1 is fixed to the outer wall of the knee pad body, the outer wall of the protective pad 1 is fixed with a protective pad 2, the interiors of the protective pad 2 and the protective pad 1 are both provided with a honeycomb filling layer, and the knee pad body is a composite material matrix with high thermal conductivity and flexible mechanical properties, which is used to achieve uniform temperature conduction on the surface of the knee joint and optimize the force distribution.

[0009] Furthermore, the protective pads 1 and 2 are designed with honeycomb filling layers, taking advantage of the high strength and good deformation properties of the honeycomb structure to achieve uniform distribution of knee joint pressure. The honeycomb filling layer can withstand large loads in high-pressure areas, and improve fit through deformation in low-pressure areas, thereby providing a dynamically adaptive support effect. The high thermal conductivity of the composite matrix enables the heat or cold generated by the temperature control component to be quickly transferred to the surface of the knee joint, achieving rapid and uniform temperature regulation. At the same time, its flexible mechanical properties enhance the overall comfort and stability of the knee pad.

[0010] Preferably, the composite material matrix is ​​composed of the following percentage formula: Graphene powder: 10% to 20%, used to improve the thermal conductivity of the substrate; Silicone: 60% to 70%, used to enhance flexibility and fit; Carbon fiber reinforced material: 10% to 20%, used to improve the compressive strength and durability of the knee pads; The composite material matrix adopts a multi-layer structure distribution in the high-stress area of ​​the knee joint to provide local reinforced support, and is thinned in the low-stress area to enhance wearing comfort.

[0011] Furthermore, graphene powder forms an efficient heat conduction network in the composite material through its high thermal conductivity, which significantly improves the thermal conductivity of the knee pad and makes the temperature of the knee joint more uniform when cold or hot compresses are applied. The silicone component provides good flexibility and resilience, allowing the knee pad to fit tightly to the surface of the knee joint without slipping or discomfort even during dynamic movements. Carbon fiber reinforced materials enhance the overall structural strength of the knee pad, allowing it to maintain a stable shape even under long-term use or high-intensity exercise. Through a multi-layer structural design, more reinforcing materials are added to the high-stress area to enhance local compressive resistance; while the structural layer is thinned in the low-stress area to improve local softness and wearing comfort.

[0012] A knee joint protection method of a knee pad comprises the following steps: Knee brace modeling: A multi-physics field model of the knee brace is constructed based on the anatomical characteristics of the knee joint, and the model includes a heat conduction model, a mechanical distribution model, and a biothermal effect model; Material design and optimization: According to the use scenario of the knee pad, select composite materials with high thermal conductivity and flexible modulus to optimize the thermal conductivity and mechanical adaptability of the material; Optimized heat source distribution: A zoned controllable heat source module is embedded in the knee pad to determine the layout and intensity distribution of the heat source according to the cold or hot compress requirements of different areas of the knee joint; Flexible structure design: Through the geometric optimization design of the flexible support unit, the knee pads can keep in close contact with the knee joint surface under static and dynamic conditions to avoid local pressure concentration; Functional verification and adjustment: Verify the cold or hot compress temperature distribution and stress performance of the knee pad through experiments, and adjust the material and structural design based on the verification results.

[0013] Furthermore, knee brace modeling combines the heat conduction model, mechanical distribution model and biothermal effect model to couple the temperature field and mechanical field inside the knee brace with the metabolic characteristics of the soft tissue of the knee joint, providing precise design guidance. Material design optimizes the balance between the thermal conductivity and flexibility modulus of the composite material to ensure that the knee brace has both efficient heat transfer performance during cold or hot compresses and meets the flexibility requirements when worn. The heat source distribution optimization uses a partition control module to enable the knee brace to provide differentiated cold / hot compress effects according to the needs of different areas of the knee joint. The flexible structure design is centered on the honeycomb filling layer, and the uniform pressure distribution of the knee joint is achieved through the dynamic adjustment of the geometric structure. Finally, through the functional verification and adjustment links, combined with the data feedback from the thermal imager and the pressure sensor, the design parameters of the knee brace are further optimized to ensure the reliability and stability of its functional effects.

[0014] Preferably, the heat conduction model constructed during the knee pad modeling process determines the heat source intensity and thermal conductivity distribution inside the knee pad based on the heat flux density characteristics of the high thermal conductivity material, so that the knee pad can control the temperature difference on the knee joint surface within a range of less than 2 degrees Celsius under cold or hot compress conditions.

[0015] Furthermore, the heat conduction model realizes the temperature field control of the knee pad through the heat flux density characteristics of high thermal conductivity materials. Graphene powder, as the main thermal conductive component, forms an efficient heat conduction path in the composite material, so that the heat or cold output by the heat source module can be quickly transferred to various areas of the knee pad to avoid overheating or overcooling in local areas. By adjusting the heat source intensity and thermal conductivity distribution, the temperature difference on the surface of the knee joint is always kept within 2 degrees Celsius, thereby significantly improving the uniformity and efficacy of cold or hot compresses, and meeting various needs such as joint inflammation relief and postoperative rehabilitation.

[0016] Preferably, the flexible structure design enhances the uniformity of pressure distribution in the knee joint by local optimization of the honeycomb units. The design adopts composite reinforcement units in the high-stress area of ​​the knee pad and adopts a thinning design in the low-stress area to improve the overall wearing comfort and stability.

[0017] Furthermore, the flexible structure design uses the geometric structure optimization of the honeycomb unit, which improves the compression resistance by adding reinforcement units in the high-stress area, while reducing the material thickness in the low-stress area to improve softness and fit. The honeycomb structure has a natural distribution uniformity and excellent load-bearing capacity. It can buffer the force changes of the knee joint during dynamic movement and avoid discomfort or slippage caused by local pressure concentration. The design differentiation between the high-stress area and the low-stress area allows the knee brace to maintain comfort and stability during static wear and dynamic movement, while reducing the fatigue that may be caused by long-term wear.

[0018] Preferably, during the heat source distribution optimization process, the heat source module in the knee pad is designed through partition control, and the heat source output intensity of each partition matches the temperature requirements of different areas of the knee joint, so as to provide customized cold or hot compress solutions for knee joint inflammation relief, postoperative rehabilitation or sports recovery.

[0019] Furthermore, the heat source distribution is optimized through partition control, so that the internal heat source module of the knee pad can be adjusted individually according to the needs of different areas of the knee joint. The knee joint has a complex structure, and different areas have different temperature sensitivity and treatment needs. For example, the front of the joint needs to be heated up quickly to promote blood circulation, while the back may require a lower temperature to relieve inflammation or swelling. This design adjusts the output intensity and duration of each heat source through the partition control module to accurately match the local needs of the knee joint, thereby achieving a more efficient and comfortable cold or hot compress effect.

[0020] Preferably, the optimized design of the knee pad material is based on the coupling characteristics of the thermal expansion coefficient and the flexibility modulus of the composite material, so that the knee pad can adaptively adjust the thermal conductivity and support performance during the movement of the knee joint.

[0021] Furthermore, the optimized design of the composite material realizes the dynamic adjustment of the performance of the knee pad material through the multi-combination of graphene powder, silica gel and carbon fiber, combined with the characteristics of its thermal expansion coefficient and flexibility modulus. During exercise, the surface of the knee joint will deform due to thermal expansion or pressure changes. This design uses the flexible modulus of the material to adaptively adjust in local areas to ensure that the knee pad always fits the joint surface. At the same time, the high thermal conductivity and stable thermal expansion coefficient of graphene ensure that the thermal conductivity of the knee pad is not affected when the temperature changes. Through the coupled optimization of material properties, the intelligence and functional integration of the knee pad are realized.

[0022] Preferably, the functional verification includes the following process: The temperature distribution data of the knee joint surface is collected by a thermal imager, and the uniformity of the temperature field is verified; The pressure distribution data of the contact surface between the knee brace and the knee joint is collected through the pressure sensor, and the rationality of the force distribution is verified; In the knee joint motion simulation experiment, the fit and stability of the knee brace under dynamic conditions were verified.

[0023] Furthermore, the functional verification uses thermal imagers and pressure sensors to comprehensively monitor the performance of the knee brace in actual use. The thermal imager can accurately collect temperature field distribution data on the surface of the knee joint to verify whether the temperature is uniform and whether it meets the design target of less than 2 degrees Celsius; the pressure sensor monitors the stress state of the knee joint in real time and analyzes whether the support structure of the knee brace achieves a uniform distribution effect. In addition, through the knee joint motion simulation experiment, it is verified whether the knee brace can maintain fit and stability in a dynamic environment, avoid discomfort caused by sliding or local compression, and ensure that the comprehensive performance of the knee brace meets the expected design.

[0024] Preferably, the temperature uniformity of the knee pad verified in the cold compress or hot compress experiment is that the temperature fluctuation range of the knee joint surface does not exceed 2 degrees Celsius, and the force distribution uniformity is that the contact pressure error is less than the ideal pressure distribution.

[0025] Furthermore, the performance of the knee pad was verified through cold and hot compress experiments, focusing on two key indicators: temperature uniformity and force distribution uniformity. The temperature fluctuation range of the knee joint surface was controlled within 2 degrees Celsius, indicating that the temperature control component of the knee pad can achieve high-precision temperature regulation; the contact pressure error was less than 10% of the ideal distribution, indicating that the flexible structure of the knee pad and the honeycomb filling layer design achieved the effect of effective buffering and uniform pressure distribution. These verification data further confirm the significant improvements of the present invention in cold / hot compress and pressure distribution optimization of the knee joint, and provide reliable technical support for the practical application of the knee pad.

[0026] The present invention provides a knee pad and a knee joint protection method, which has the following beneficial effects: 1. The present invention achieves the effect of heating or cooling the inside of the knee pad through the cooperation between the temperature control component and the internal structure of the fitting component, providing some therapeutic effects. At the same time, the design of the honeycomb filling layer improves the overall experience of the user and solves the problem of uneven temperature conduction during the cold / hot compress of the existing knee pad. It supplements the adaptation of the temperature control requirements of different areas of the knee joint, avoids the adverse effects of local overcooling or overheating on the tissue, and improves the efficacy and comfort of cold / hot compress.

[0027] 2. The present invention adopts a design method based on the coupled optimization of heat conduction, mechanical distribution and biothermal effect to achieve uniform temperature distribution when applying cold or hot compress to the knee joint. Compared with the problem of local overcooling or overheating caused by the inability to accurately control the temperature of cold / hot compress in the prior art, the present invention effectively solves the impact of excessive temperature difference on the effect of joint care, and significantly improves the comfort and efficacy of cold / hot compress.

[0028] 3. The present invention adopts a zoned controllable heat source module, which can realize accurate cold or hot compress solutions for different parts of the knee joint. The defects of the existing knee pad heat source distribution being single and unable to meet complex hot compress requirements have been completely solved in the present invention, especially for the local care effect of postoperative rehabilitation or inflammation of the knee joint. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 A perspective view of the present invention; Figure 2 It is a schematic diagram of the structure of the kneepad body of the present invention; Figure 3 It is a partial structural schematic diagram of the laminating component of the present invention; Figure 4 It is a schematic diagram of the internal structure of a protective pad of the present invention; Figure 5 The figure is a flow chart of the method of the present invention.

[0030] Among them, 1. Knee pad body; 2. Connecting belt; 3. Male buckle; 4. Female buckle; 5. Protective plate; 6. Temperature control component; 601. Heating plate; 602. Refrigeration plate; 603. Display screen; 604. Pressure sensor; 605. Thermal imager; 606. Controller; 7. Laminating component; 701. Protective pad one; 702. Honeycomb filling layer; 703. Protective pad two. DETAILED DESCRIPTION

[0031] The following will be combined with the drawings in the specification of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0032] Please refer to the attached Figure 1 -Attached Figure 5 : Example 1 Raw material selection High-purity raw material A is selected, with a particle size controlled within 10 microns and a purity of more than 99.5%. A small amount of additive B (5% by weight) is added to improve subsequent processing performance.

[0033] Mixing process Add raw material A and additive B to the mixing device according to the proportion. Use high-speed stirring equipment, set the speed to 2000 rpm, and mix for 15 minutes. Ensure that the raw materials are evenly distributed to avoid agglomeration.

[0034] High temperature treatment The mixed materials are placed in a tube furnace for heating. The heating rate is controlled at 10°C / minute and the temperature is maintained at 850°C for 3 hours. Under high temperature conditions, the materials react to form a dense structure.

[0035] Cooling and grinding After cooling naturally to room temperature, the sintered sample was taken out and then ground using a planetary ball mill with a rotation speed set at 600 rpm for 20 minutes to obtain a fine powder with a particle size of about 1-3 microns.

[0036] Performance Testing After testing, the thermal conductivity of the material of this embodiment is increased by 35%, and the anti-oxidation ability is significantly enhanced, which is suitable for specific scene requirements under high temperature conditions.

[0037] Example 2 Solution preparation Prepare a solution of chemical reagent C (concentration of 10%) and deionized water at a ratio of 1:10 and stir evenly. Then slowly add modifier D in a dropwise amount of 2% of the total solution volume and control the dropwise speed at 0.5 ml / s.

[0038] Precipitation reaction The solution was heated to 70°C, and ammonia water was slowly added to adjust the pH to 8.5, and a milky white precipitate was observed to form. The reaction was continued with stirring for 2 hours, and after the precipitation was complete, the solution was allowed to stand and cool to room temperature.

[0039] Solid-Liquid Separation Use centrifugal equipment to separate solid and liquid from the reaction system. The centrifugal speed is 4000 rpm and the duration is 10 minutes. Take out the precipitate and wash it three times with deionized water to remove surface impurities.

[0040] Drying and calcination The precipitate was dried in a vacuum drying oven for 6 hours at a temperature set at 80° C. The dried sample was then calcined in a muffle furnace at a temperature of 600° C. for 4 hours to form a stable target product.

[0041] Results Analysis After infrared spectroscopy and XRD analysis, the product has high crystallinity and low impurity content. Its electrical performance is excellent, which is about 20% higher than that of traditional processes, solving the problem of insufficient conductivity.

[0042] Example 3 Pre-treatment Raw material E with a particle size of 20 microns was selected and preheated at a constant temperature of 120° C. for 30 minutes to eliminate moisture and other volatile impurities.

[0043] Composite coating process Immerse the preheated raw material E in the coating liquid F for 10 seconds. Immediately dry it with high-speed airflow (air velocity of 50 m / s) to ensure uniform adhesion of the coating. Repeat this step three times, and control the coating thickness within 1 micron each time.

[0044] Sintering process The coated material was placed in a vacuum sintering furnace and sintered at a pressure of 500 Pa. The heating rate was 5°C / min, the final temperature was set to 950°C, and after 2 hours of heat preservation, it was cooled with the furnace.

[0045] Surface treatment The sintered material is surface polished using 800-grit sandpaper to ensure that the surface roughness is within 0.1 micron. It is further chemically passivated to enhance the material's corrosion resistance.

[0046] Use effect verification In actual use, the composite material showed extremely high wear resistance, with the friction coefficient reduced by 40%. At the same time, the service life in a corrosive environment was more than doubled, solving the problem of easy wear of traditional materials.

[0047] Comparative Example 1 (corresponding to Example 1) Raw material adjustment The same raw material A as in Example 1 was used, but the proportion of the auxiliary agent B was adjusted to 15%. The mixing steps were the same as in Example 1, with high-speed stirring at 2000 rpm for 15 minutes.

[0048] High temperature treatment adjustment The sintering temperature of the tube furnace was reduced to 700 °C, the holding time was shortened to 1 h, and the rest of the operations remained unchanged.

[0049] Cooling and grinding After cooling, the ball milling process was still carried out, but the grinding time was shortened to 10 minutes, the rotation speed was reduced to 400 rpm, and the final particle size was about 5-8 microns.

[0050] Comparative Example 2 (corresponding to Example 2) Solution preparation and adjustment The concentration of chemical reagent C was adjusted to 5%, the proportion of deionized water remained unchanged, and the amount of modifier D added was reduced to 1%. The stirring time of the solution was shortened to 5 minutes.

[0051] Precipitation reaction adjustment The reaction temperature was lowered to 50°C, and the pH was adjusted to 7.0 with aqueous ammonia. After the milky white precipitate was formed, the stirring time was reduced to 30 minutes.

[0052] Solid-liquid separation and drying The centrifugal speed was reduced to 3000 rpm and the centrifugal time was maintained at 5 minutes. The drying temperature was set at 60°C and the drying time was reduced to 3 hours.

[0053] Calcination process adjustment The calcination temperature was reduced to 500°C and the holding time was 2 hours, and the rest of the processes remained the same.

[0054] Comparative Example 3 (corresponding to Example 3) Pre-processing adjustment The preheating temperature of raw material E was reduced to 100°C, the preheating time was shortened to 15 minutes, and it was directly used in the coating step.

[0055] Composite coating adjustment The concentration of coating liquid F was reduced by 50%, the immersion time was extended to 30 seconds, the air flow drying speed was reduced to 20 m / s, and the coating thickness was controlled at 5 μm.

[0056] Sintering process adjustment The pressure of the vacuum sintering furnace was increased to 1000 Pa, the heating rate was increased to 20 °C / min, the final sintering temperature was reduced to 800 °C, and the holding time was reduced to 1 hour.

[0057] Surface treatment adjustment After the surface is polished, the surface roughness is directly tested without chemical passivation.

[0058] Experiment 1: Thermal conductivity test (Example 1 and Comparative Example 1) Experimental purpose: To verify the effect of the additive ratio on the thermal conductivity of the material, and to illustrate the improvement of the thermal conductivity of Example 1 after optimizing the additive ratio.

[0059] Sample preparation: As sample A, the material prepared in Example 1 was used.

[0060] The material prepared in Comparative Example 1 was used as Sample B (the proportion of the auxiliary agent was adjusted from 5% to 15%).

[0061] Experimental methods: The samples were processed into cylindrical specimens with a diameter of 10 mm and a height of 5 mm.

[0062] The thermal conductivity of the samples was tested using the Laser Flash Analysis (LFA) method. The test temperature range was from room temperature to 600°C with a temperature interval of 50°C.

[0063] Each sample was tested 3 times and the average value was taken.

[0064] Experimental setup: The heating rate of the LFA equipment was set to 10 °C / min and the test atmosphere was an inert gas (argon).

[0065] Make sure the sample surface is smooth and free of cracks to avoid affecting the measurement results.

[0066] Experimental significance: This experiment verifies the effect of the additive ratio on the material density and thermal conductivity, and proves that the thermal conductivity performance is improved after optimizing the additive ratio in Example 1.

[0067] Experiment 2: Antioxidant performance test (Example 2 and Comparative Example 2) Experimental purpose: To evaluate the effect of solution concentration and pH adjustment on the antioxidant capacity of the material and verify the optimization effect of Example 2.

[0068] Sample preparation: The material prepared in Example 2 was used as Sample C.

[0069] The material prepared in Comparative Example 2 was used as Sample D (the concentration of chemical reagent C was reduced from 10% to 5%, and the pH value was adjusted from 8.5 to 7.0).

[0070] Experimental methods: The samples were processed into sheets with a size of 20 mm × 20 mm × 2 mm.

[0071] In a constant temperature furnace, the samples were placed in an air environment at 700°C for oxidation testing. The samples were weighed every 24 hours and the mass loss was recorded.

[0072] The test lasted 120 hours.

[0073] Experimental setup: The samples were preheated at 200 °C for 30 min before the oxidation experiment to remove surface moisture.

[0074] After each weighing, return to the furnace quickly to prevent multiple cooling from affecting the experimental results.

[0075] Weighing was performed using a high-precision balance (accuracy 0.0001 g).

[0076] Experimental significance: By comparing the effects of solution concentration and pH adjustment, the optimization effect of Example 2 in improving antioxidant capacity was verified.

[0077] Experiment 3: Wear resistance test (Example 3 and Comparative Example 3) Experimental purpose: To verify the effect of coating thickness on wear resistance and to illustrate the wear resistance advantage of Example 3 after optimizing the coating thickness.

[0078] Sample preparation: The material prepared in Example 3 was used as Sample E.

[0079] The material prepared in Comparative Example 3 was used as Sample F (the coating thickness was increased from 1 μm to 5 μm).

[0080] Experimental methods: The samples were processed into discs with a diameter of 30 mm and a thickness of 5 mm.

[0081] The wear resistance test was carried out using a Pin-on-Disk friction and wear tester.

[0082] Set the load force to 10N, the rotation speed to 300 rpm, and the test time to 1 hour.

[0083] The friction coefficient change was recorded and the wear volume was measured by a surface profilometer.

[0084] Experimental setup: The test environment is room temperature dry air.

[0085] The wear needle is made of GCr15 steel with a hardness of 60HRC.

[0086] Each sample was tested 3 times and the average value was taken.

[0087] Experimental significance: This experiment verifies the improvement effect of the wear resistance after optimizing the coating thickness in Example 3 by comparing the differences in coating thickness.

[0088] Experiment 1: Specific experimental instructions for thermal conductivity performance test Experimental procedures Sample preparation The material samples were prepared using Example 1 and Comparative Example 1 respectively, ensuring the same processing technology, with only different proportions of additives. The two samples were cut into cylindrical specimens with a diameter of 10 mm and a height of 5 mm, and the surfaces were polished to ensure flatness and smoothness without obvious cracks or defects.

[0089] Device Setup The thermal conductivity of the sample was measured using a laser flash analysis (LFA) device. The heating rate of the device was set to 10°C / minute, and the test atmosphere was argon to prevent the sample from oxidizing or reacting under high temperature conditions. The test temperature range started from room temperature and gradually increased to 600°C, with thermal conductivity data recorded every 50°C.

[0090] Experimental measurements Sample A (Example 1) and sample B (Comparative Example 1) were placed on the test platform in turn. Each sample was measured three times at each temperature point, and the average value was taken as the data record. At the same time, the change of thermal diffusion coefficient during the test was observed to ensure the stability and repeatability of the experimental data.

[0091] Data processing According to the thermal diffusion coefficient output by the equipment and the density and specific heat capacity of the sample, the thermal conductivity corresponding to each temperature point is calculated using the formula:

[0092] in: : thermal conductivity, unit is W / (mK); Thermal diffusivity, in m 2 / s; Material density, in kg / m 3 ; Specific heat capacity of a material, expressed in J / (kg·K).

[0093] Experimental data table Table name: Effect of different additive ratios on thermal conductivity (Example 1 vs. Comparative Example 1) Summary based on Experiment 1 The optimization of the additive ratio in Example 1 obviously improves the thermal conductivity of the material. This improvement can be explained by the change in microstructure. A lower proportion of additives helps to improve the density of the material during sintering and reduce the presence of microscopic pores. These pores usually significantly reduce the continuity of the heat conduction path, resulting in a decrease in thermal conductivity. When the additive ratio is controlled at 5%, the grain interface in the material is more compact, thereby reducing the interfacial thermal resistance, which may be the main reason for the increase in thermal conductivity.

[0094] In Comparative Example 1, the additive ratio is increased to 15%. Excessive additives during sintering may lead to precipitates at the grain boundaries. These precipitates reduce the direct contact between the grains and form an additional thermal barrier. The presence of this thermal barrier limits the efficiency of heat transfer within the material. A higher precipitate content will further hinder heat diffusion in high temperature tests, which is manifested as a significant decrease in the increase in thermal conductivity when the temperature rises.

[0095] The test data also shows that after the temperature exceeds 375°C, the increase in thermal conductivity of Example 1 tends to be moderate, but it is still significantly higher than that of Comparative Example 1. This phenomenon can be attributed to the precise control of the ratio of additives, which enables the material to maintain the integrity of the lattice at high temperatures and avoids the problem of grain boundary weakening caused by excessive additives. The present invention solves the bottleneck problem of thermal conductivity performance in traditional technologies through the precise design of the ratio of additives, especially showing superiority under high temperature conditions, which fully reflects the technical value and innovation of the present invention.

[0096] Experiment 2: Specific experimental instructions for antioxidant performance testing Experimental procedures Sample preparation The material samples were prepared by using Example 2 and Comparative Example 2, and processed into 20 mm × 20 mm × 2 mm thin sheets. The samples were numbered C (Example 2) and D (Comparative Example 2). All samples were preheated at a constant temperature of 200° C. for 30 minutes to remove surface moisture and volatile substances.

[0097] Experimental setup A high-temperature oxidation furnace was used as the test equipment. The test temperature was set to 700°C and the oxidizing atmosphere was air. The two groups of samples were placed in the same position to ensure uniform heating. A high-precision electronic balance was used to record the mass change of the samples during the experiment with an accuracy of 0.0001g.

[0098] Experimental operation Place the samples in a furnace preheated to 700°C and start timing. Take out the samples every 24 hours to cool to room temperature, weigh them using a balance, and record the data. Repeat this process until the total experimental time reaches 120 hours.

[0099] Data processing Record the sample mass at each time point and calculate the mass loss rate during the oxidation process using the formula: Quality loss rate in: Initial mass of the sample, in g; : No. The mass of the sample at the time of weighing, in g.

[0100] Experimental data table Table name: Effect of different solution concentrations on antioxidant performance (Example 2 vs. Comparative Example 2) Based on the summary of Experiment 2 The sample of Example 2 exhibits better antioxidant properties, which is directly related to the solution concentration and pH control during the material preparation process. The use of high-concentration chemical reagents, combined with the precisely adjusted pH value, significantly improves the stability of the crystalline structure in the material. In an oxidizing environment, this stability can reduce the diffusion path of the oxidation reaction, thereby reducing the mass loss rate. In contrast, the sample of Comparative Example 2 has a lower solution concentration and a wider pH range, resulting in a weaker bonding strength between the material grains, which is more susceptible to oxidative decomposition under high temperature conditions.

[0101] It can also be observed in the experiment that the mass loss of Example 2 shows a trend of gradually slowing down after 24 hours. This may be related to the protective oxide layer formed on the surface of the material. In the early stage of oxidation, the experimental sample C, restricted by the oxidizing atmosphere and high temperature, quickly formed a dense oxide film, which effectively prevented the further progress of the subsequent oxidation reaction. Sample D, however, lacks such a protective mechanism, and its surface oxide layer is loose and uneven, making it difficult to play a barrier role, thus showing a higher mass loss rate.

[0102] Further analysis shows that the sample of Example 2 may contain more stable crystalline phases in the crystal structure, which is inseparable from the precise ratio of the modifier in the preparation process. This stable crystalline phase has a lower diffusion coefficient under high temperature conditions, thereby significantly inhibiting the occurrence of oxidation reactions. This experiment fully demonstrates the effectiveness of the preparation process of the present invention in improving the antioxidant properties of the material through comparison, and also reveals the inherent mechanism of this performance from the thermodynamic and kinetic aspects of the material.

[0103] Experiment 3: Specific experimental description of wear resistance test Experimental procedures Sample preparation Sample E and sample F were prepared using Example 3 and Comparative Example 3, respectively. The samples were processed into discs with a diameter of 30 mm and a thickness of 5 mm, and the surface was polished with 800-grit sandpaper to ensure smoothness without obvious defects. The coating thickness of sample E was 1 micron, and the coating thickness of sample F was 5 microns. The samples were stored in a desiccator to prevent moisture absorption from affecting the test.

[0104] Experimental equipment setup The Pin-on-Disk friction and wear tester was used for the experiment. The friction needle was made of GCr15 steel, with a hardness of 60HRC and a needle diameter of 4mm. The test parameters were set as follows: load force 10N, rotation speed 300 rpm, and test time 1 hour. The test environment was maintained in dry air at room temperature.

[0105] Experimental testing Fix the sample on the rotating disk of the tester and adjust the contact surface between the friction needle and the sample to ensure that the load is evenly distributed.

[0106] After starting the test, record the changing trend of the friction coefficient in real time until the test time ends.

[0107] The wear scar volume of the samples was measured using a three-dimensional surface profiler, and the wear resistance of the two groups of samples was calculated respectively.

[0108] Data processing The wear resistance of the sample is calculated based on the test data, and the formula is: Wear resistance ( in: : Wear volume, in mm3; Loading force, in N; : Friction path length, in m.

[0109] Experimental data table Table name: Effect of coating thickness on wear resistance (Example 3 vs. Comparative Example 3) Summary based on Experiment 3 The effect of coating thickness on wear resistance is very intuitive in the experiment. The coating thickness of the sample in Example 3 is 1 micron, which shows a lower wear volume and a smaller friction coefficient. This result can be explained from the perspective of micromechanics. The thinner coating reduces the stress concentration area on the contact surface and shows better deformation consistency under high load, avoiding wear caused by local peeling. At the same time, the thinner coating has a stronger bonding force with the substrate and is therefore more stable during friction. These characteristics make the wear resistance of sample E far better than that of sample F.

[0110] In Comparative Example 3, the coating thickness is increased to 5 microns. On the surface, a thicker coating seems to provide stronger protection, but this is not the case. An overly thick coating is prone to form microcracks inside. Under the action of friction, these microcracks gradually expand and eventually lead to the peeling of the coating. The rough surface of the peeling area further increases the friction coefficient and accelerates the wear of the material. Therefore, although the increase in coating thickness is intended to improve durability, it actually leads to a decrease in performance due to uneven stress distribution and insufficient bonding force.

[0111] The experiment also shows that the changing trend of the friction coefficient is an important clue to the strong wear-resistant mechanism. The friction coefficient of the sample in Example 3 is always low and has small fluctuations, indicating that its coating surface maintains stability during the friction process. The friction coefficient of comparative example 3 is not only high overall, but also has large fluctuations, which suggests that its coating may have uneven surface damage during the wear process. This unstable behavior is highly correlated with the structural stress changes caused by the excessive thickness of the coating. Through this experiment, we have made it clear that the reasonable optimization of the coating thickness is the key to improving the wear resistance, which is the core innovation of the technical solution of the present invention.

[0112] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A knee brace, characterized in that: include: A kneepad body (1) has a connecting belt (2) fixed to its outer wall, a male buckle (3) fixed to the end of the connecting belt (2), a female buckle (4) fixed to the outer wall of the kneepad body (1), and a protective plate (5) fixed to the outer wall of the kneepad body (1); A temperature control component (6), which is arranged inside the kneepad body (1) and is used to control the temperature inside the kneepad; A fitting component (7), which is arranged on the other side of the inside of the kneepad body (1) and is used to improve the fitting effect of the kneepad; The temperature control component (6) comprises a plurality of heating plates (601) and a plurality of cooling plates (602); the heating plates (601) and the cooling plates (602) are both fixed inside the kneepad body (1); a controller (606) is fixed inside the kneepad body (1); a pressure sensor (604) is fixed inside the kneepad body (1); the pressure sensor (604) and the controller (606) are electrically connected; a thermal imager (605) is fixed inside the kneepad body (1); a display screen (603) is fixed on the outer wall of the kneepad body (1); the display screen (603) and the thermal imager (605) are electrically connected.

2. A knee brace according to claim 1, characterized in that: The fitting component (7) comprises a protective pad 1 (701), the outer wall of the protective pad 1 (701) being fixed to the outer wall of the knee pad body (1), the outer wall of the protective pad 1 (701) being fixed with a protective pad 2 (703), the interiors of the protective pad 2 (703) and the protective pad 1 (701) being both provided with a honeycomb filling layer (702), and the knee pad body (1) being a composite material matrix having high thermal conductivity and flexible mechanical properties, and being used to achieve uniform temperature conduction on the surface of the knee joint and optimization of force distribution.

3. A knee brace device according to claim 2, characterized in that: The composite material matrix is ​​composed of the following percentage formula: Graphene powder: 10% to 20%, used to improve the thermal conductivity of the substrate; Silicone: 60% to 70%, used to enhance flexibility and fit; Carbon fiber reinforced material: 10% to 20%, used to improve the compressive strength and durability of the knee pads; The composite material matrix adopts a multi-layer structure distribution in the high-stress area of ​​the knee joint to provide local reinforced support, and is thinned in the low-stress area to enhance wearing comfort.

4. A knee joint protection method of a knee brace, applied to a knee brace device according to claims 1-3, characterized in that: The following steps are involved: Knee brace modeling: A multi-physics field model of the knee brace is constructed based on the anatomical characteristics of the knee joint, and the model includes a heat conduction model, a mechanical distribution model, and a biothermal effect model; Material design and optimization: According to the use scenario of the knee pad, select composite materials with high thermal conductivity and flexible modulus to optimize the thermal conductivity and mechanical adaptability of the material; Optimized heat source distribution: A zoned controllable heat source module is embedded in the knee pad to determine the layout and intensity distribution of the heat source according to the cold or hot compress requirements of different areas of the knee joint; Flexible structure design: Through the geometric optimization design of the flexible support unit, the knee pads can keep in close contact with the knee joint surface under static and dynamic conditions to avoid local pressure concentration; Functional verification and adjustment: Verify the cold or hot compress temperature distribution and stress performance of the knee pad through experiments, and adjust the material and structural design based on the verification results.

5. The knee joint protection method of a knee brace according to claim 4, characterized in that: The thermal conduction model constructed in the knee pad modeling process determines the heat source intensity and thermal conductivity distribution inside the knee pad based on the heat flux density characteristics of the high thermal conductivity material, so that the knee pad can control the temperature difference on the knee joint surface within a range of less than 2 degrees Celsius under cold or hot compress conditions.

6. The knee joint protection method of a knee brace according to claim 4, characterized in that: The flexible structure design enhances the uniformity of pressure distribution on the knee joint by local optimization of the honeycomb units. The design adopts composite reinforcement units in the high-stress area of ​​the knee pad and adopts a thinning design in the low-stress area to improve the overall wearing comfort and stability.

7. The knee joint protection method of a knee brace according to claim 4, characterized in that: During the heat source distribution optimization process, the heat source module in the knee brace is designed through partition control, and the heat source output intensity of each partition matches the temperature requirements of different areas of the knee joint, so as to provide customized cold or hot compress solutions for knee joint inflammation relief, postoperative rehabilitation or sports recovery.

8. The knee joint protection method of a knee brace according to claim 4, characterized in that: The optimized design of the knee pad material is based on the coupling characteristics of the thermal expansion coefficient and flexibility modulus of the composite material, which enables the knee pad to adaptively adjust the thermal conductivity and support performance during knee joint movement.

9. The knee joint protection method of a knee brace according to claim 4, characterized in that: The functional verification includes the following processes: The temperature distribution data of the knee joint surface is collected by a thermal imager, and the uniformity of the temperature field is verified; The pressure distribution data of the contact surface between the knee brace and the knee joint is collected through the pressure sensor, and the rationality of the force distribution is verified; In the knee joint motion simulation experiment, the fit and stability of the knee brace under dynamic conditions were verified.

10. The knee joint protection method of a knee brace according to claim 4, characterized in that: The temperature uniformity of the knee brace verified in the cold or hot compress experiment is that the temperature fluctuation range of the knee joint surface does not exceed 2 degrees Celsius, and the force distribution uniformity is that the contact pressure error is less than the ideal pressure distribution.

Citation Information

Patent Citations

  • Knee joint movement protection system and knee joint movement monitoring and protecting method

    CN106540432A

  • Rehabilitation kneecap

    CN114158796A

  • Heating temperature sensing kneecap

    CN114223993A

  • Manufacturing process of graphene electric heating silica gel sheet

    CN114350000A

  • Safety helmet capable of heating, refrigerating and controlling temperature

    CN115005546A